Mister Exam

Other calculators

(6x-24)*(x+19)=0 equation

The teacher will be very surprised to see your correct solution 😉

v

Numerical solution:

Do search numerical solution at [, ]

The solution

You have entered [src]
(6*x - 24)*(x + 19) = 0
(x+19)(6x24)=0\left(x + 19\right) \left(6 x - 24\right) = 0
Detail solution
Expand the expression in the equation
(x+19)(6x24)=0\left(x + 19\right) \left(6 x - 24\right) = 0
We get the quadratic equation
6x2+90x456=06 x^{2} + 90 x - 456 = 0
This equation is of the form
a*x^2 + b*x + c = 0

A quadratic equation can be solved
using the discriminant.
The roots of the quadratic equation:
x1=Db2ax_{1} = \frac{\sqrt{D} - b}{2 a}
x2=Db2ax_{2} = \frac{- \sqrt{D} - b}{2 a}
where D = b^2 - 4*a*c - it is the discriminant.
Because
a=6a = 6
b=90b = 90
c=456c = -456
, then
D = b^2 - 4 * a * c = 

(90)^2 - 4 * (6) * (-456) = 19044

Because D > 0, then the equation has two roots.
x1 = (-b + sqrt(D)) / (2*a)

x2 = (-b - sqrt(D)) / (2*a)

or
x1=4x_{1} = 4
x2=19x_{2} = -19
Sum and product of roots [src]
sum
-19 + 4
19+4-19 + 4
=
-15
15-15
product
-19*4
76- 76
=
-76
76-76
-76
Rapid solution [src]
x1 = -19
x1=19x_{1} = -19
x2 = 4
x2=4x_{2} = 4
x2 = 4
Numerical answer [src]
x1 = -19.0
x2 = 4.0
x2 = 4.0